Integrating Arabic Language and Qur’anic Exegesis Learning in Salaf-Modern Islamic Boarding Schools: A Multisite Study in Jombang - Asep Maulana; Ainul Churria al-Malachim (UIN Sunan Gunung Djati Bandung, 2026)
Despite the central role of Arabic in understanding the Qur’an, studies on its systematic integration with tafsir instruction in Indonesian Salaf-Modern Islamic boarding schools remain limited. This gap highlights the absence of a well-documented contextual integrative learning model that connects Arabic linguistic competence with Qur’anic exegesis in pesantren contexts. This study develops and analyzes a contextual Arabic–tafsir integrative learning model implemented in two Salaf-Modern Islamic boarding schools in Jombang, Indonesia: Darul Ulum and Al-Munawaroh. It investigates the implementation process and the supporting and inhibiting factors influencing its effectiveness. Using a qualitative multisite design, data were collected through observations, interviews, and document analysis involving Arabic and tafsir teachers. The findings indicate that both institutions apply an integrative Arabic–tafsir learning model that positions Arabic as a medium for direct Qur’anic comprehension within a contextual and competency-based framework. Although both institutions share similar objectives, they differ in implementation orientation: Darul Ulum emphasizes structured Arabic linguistic sciences, while Al-Munawaroh prioritizes language habituation, motivational reinforcement, and flexible nonformal learning practices. The effectiveness of the model is shaped by teacher competence, institutional commitment, learning resources, and student motivation, whereas heterogeneous student backgrounds, limited instructional time, and insufficient professional development hinder its implementation. This study contributes a contextual integrative Arabic–tafsir learning model as a pedagogical framework for curriculum development in Islamic education, particularly in pesantren contexts, and provides a basis for further empirical validation and scalability studies